2012
DOI: 10.1002/adsc.201100392
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Studies of Iron‐Catalyzed Cross‐Coupling of Alkyl Grignard Reagents with Aryl Electrophiles

Abstract: Abstract:The title reaction has been studied under low temperature conditions. Coupling with active substrates can be done even at dry ice temperature. Initial rate studies at À25 8C indicate that high concentrations of any reagent can lead to either complete or partial catalyst deactivation. Under strongly reducing conditions, iron seems to form less active complexes that only slowly re-enter the catalytic cycle, possibly through bimolecular coupling of iron(II) complexes. Computational studies support the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 58 publications
(23 reference statements)
5
20
0
Order By: Relevance
“…The same conclusion was drawn from low temperature studies of the reaction of aryl electrophiles with alkyl Grignard reagents. 426 Kinetic investigations were in agreement with an Fe(I)/Fe(III) catalytic cycle. Moreover, it could be shown that an excess of Grignard reagent leads to reduced iron complexes which are less active in the cross coupling reaction.…”
Section: Scheme 202supporting
confidence: 66%
“…The same conclusion was drawn from low temperature studies of the reaction of aryl electrophiles with alkyl Grignard reagents. 426 Kinetic investigations were in agreement with an Fe(I)/Fe(III) catalytic cycle. Moreover, it could be shown that an excess of Grignard reagent leads to reduced iron complexes which are less active in the cross coupling reaction.…”
Section: Scheme 202supporting
confidence: 66%
“…faster oxidative addition) or appropriate stabilizing ligands/additives can serve to minimize the unproductive aggregation of the lowvalent iron species. 77 In the present case, it may be that the relatively unreactive nature of thio ether 3d (with respect to alkyl halides) and the lack of a stabilizing ligand/additive may serve to enable catalyst deactivation.…”
Section: Discussionmentioning
confidence: 89%
“…8m,74 However, in the case of aryl Grignard reagents, there is no conclusive evidence that oxidation states as low as Fe(–II) are kinetically accessible from Fe(II) or Fe(III) pre-catalysts under the conditions generally employed in preparative cross-coupling reactions. An Fe(I)/Fe(III) catalytic cycle, originally proposed by Kochi on the basis of by-product analysis and EPR measurements, 75 has been suggested to be the most plausible pathway (at least under the specific reaction conditions) in the cross-coupling of alkyl halides 76 and aryl halides 77 with alkyl Grignard reagents, and benzyl halides with arylzinc reagents. 78 An Fe(II)/Fe(III) catalytic cycle for the cross-coupling of aryl Grignard reagents with alkyl halides in the presence of TMEDA has also found experimental support in studies of isolated organoiron species.…”
Section: Discussionmentioning
confidence: 99%
“…Excellent efficiency and regioselectivity were found for the reactions cinnamyl substrate (1o)w ith both aromatic and alkyl Grignardr eagents (entries [13][14][15][16]. Another important feature of this directing CÀOb ond stetagy is that other functionalized and unreactive allylic ethers [15] (1p-1 s)r eacted smoothly with 2a under the present reaction conditions (entries [17][18][19][20].…”
mentioning
confidence: 69%